PEMBERIAN CORE STABILITY EXERCISE KOMBINASI HEEL RAISES EXERCISE SAMA BAIK DENGAN CORE STABILITY EXERCISE KOMBINASI ANKLE STRATEGY EXERCISE TERHADAP KESEIMBANGAN STATIS ANAK FLAT FOOT USIA 9-11 TAHUN DI SEKOLAH DASAR NEGERI 4 TONJA DENPASAR - Made Risma Caesar Witayanti; Ni Luh Nopi Andayani; Ni Wayan Tianing (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACTFlat foot is a flat arch that can disturb the static balance in children aged 9-11 years. Interventions that can be givenare core stability exercise, heel raises exercise and ankle strategy exercise. The result of hypothesis test withpaired sample t-test on Group Core Stability Exercise combination of Heel Raises Exercise got increase 104,5 secondswith value p = 0,001, while at Group Core Stability Exercise combination of Ankle Strategy Exercise got increase90,11 seconds with value p = 0.001. Test the difference of two groups increase using independent t-test with pvalue = 0,031. These results indicate that there is no significant difference in improving the static balance in flat footchildren between the two groups.Keywords: Balance, Flat foot, Core Exercise, Heel Raises Exercise, Ankle Strategy Exercise.